A core-shell structured Fe2O3/ZrO2@ZrO2 nanomaterial with enhanced redox activity and stability for CO2 conversion. (January 2017) - Hu, Jiawei; Galvita, Vladimir V.; Poelman, Hilde; Detavernier, Christophe; Marin, Guy B.
Graphical abstract: Highlights: A core-shell structured Fe2 O3 /ZrO2 @ZrO2 nanomaterial is synthesized by a combination of nanocoating and impregnation methods. The evolution of iron oxides to metallic iron in Fe2 O3 /ZrO2 @ZrO2 is followed by in situ XRD as a function of temperature. Fe2 O3 /ZrO2 @ZrO2 shows superior redox activity, excellent structural stability and strong capability to resist sintering in CO2 conversion to CO compared to the material without coating. Abstract: A novel Fe2 O3 /ZrO2 @ZrO2 nanomaterial with core-shell structure is proposed, where first Fe2 O3 nanoparticles are loaded onto a ZrO2 support as a core and afterwards the core is coated with a thin and porous layer of ZrO2 . Such combination of nanocoating and impregnation methods has been applied to synthesize core-shell oxygen storage nanomaterials with different iron oxide loading. 2D in-situ XRD patterns recorded during isothermal redox cycles at different temperatures (550–650 °C) show the evolution of Fe3 O4 to metallic iron in Fe2 O3 /ZrO2 @ZrO2 as a function of temperature. A detailed characterization of fresh and spent samples demonstrates that the Fe2 O3 /ZrO2 @ZrO2 materials exhibit excellent structural stability (stable pore structure, specific surface area and core-shell morphology) and strong capability to resist sintering after 100 redox cycles at 650 °C for CO2 conversion to CO compared to the samples prepared by impregnation only. The strong thermal stability of ZrO2 coating materials contributes to keep up the activity of active phase during high-temperature environments.